The Relationship of Mental Readiness of Primigravida Pregnant Women with the Level of Anxiety Before Childbirth - Susilawati (Bulletin of Inspiring Developments and Achievements in Midwifery, 2024)
Mental readiness is an important factor influencing the psychological state of pregnant women before delivery. In primigravida mothers, lack of experience and knowledge about the labor process often triggers increased anxiety. Anxiety in the period before delivery can impact the smoothness of the labor process, the mother's ability to adapt, and the well-being of the fetus. This study aims to determine the relationship between the mental readiness of primigravida pregnant women and the level of anxiety before delivery in the work area of ​​the Ambacang Padang Community Health Center. The study used a descriptive analytical design with a cross-sectional approach. A total of 40 primigravida pregnant women were selected through a purposive sampling technique. The research instruments were a mental readiness questionnaire and an anxiety level questionnaire. Data analysis was performed univariately to describe the characteristics of the respondents and bivariately using the Chi-Square test. The results showed that 26 respondents (65%) had low mental readiness and 14 respondents (35%) had high mental readiness. The anxiety levels consisted of low (15%), moderate (45%), and high (40%). The Chi-Square test showed a significant relationship between mental readiness and anxiety levels (p < 0.05). Mothers with low mental preparedness are more likely to experience moderate to high levels of anxiety. This finding underscores the importance of midwives' role in providing antenatal education, childbirth preparation counseling, and psychological support to improve mental preparedness and reduce anxiety.